THE STUDY OF NEW COMPOSITES WITH GRAPHENE USED IN DENTISTRY - SAVA, Sorina; SAROSI, Codruta; BOBOIA (CUC), Stanca; TONEA, Andrada; ALB, Camelia; DUDEA, Diana (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The development of graphene nanopowder in a polymer matrix has opened, in recent years, a new and exciting area in the science of dental materials. Physico-chemical and mechanical properties of these materials are improved at a very low filler loading in the polymer matrix. The novelty of this study is the utilization of graphene-silver nanopowder as filler in new dental composites to improve the physico-mechanical properties. Three experimental composites, two with different percent in graphene-silver nanopowder and one commercial nanohybrid composite Herculite XRV Ultra (Kerr) were investigated by water absorption and solubility in distilled water and artificial saliva (1, 7, 14 and 21 days), respectively flexural strength and Young’s modulus properties. One-way analysis of variance (ANOVA) test, for multiple comparisons between means to determine significant differences was used at a significance level set at p≤0.05. The experimental results show that composite with a greater amount of graphene (G2) present better results of water absorbtion and flexural strength.